靈樞·海論에 대한 연구 - 정동수(Dong Su Jeong); 정헌영(Heon Young Jeong) (동의생리병리학회지, 2006)
Hae Ron(海論) was recorded to Tae So(太素)'s volume 5 Sa-hae-hap(四海合), Gap Eul(甲乙)'s volume 1 chapter 8 Sahae(四海) and You Gyeong(類經)'s volume 9 Gyung-lak-ryu-sam-sib-yi(經絡類三十二) Yin-ji-sa-hae(人之四海). Human body has the Sahae(四海; Gi hae, Heul hae, Sugok hae, Su hae) as like as Earth has Sahae(四海; East sea, West sea, South sea, North sea). Person's Sahae corresponds with Earth's Sahae. This Chapter is explaining about Acupoint's position that Sahae's Gi-hyeol(氣血) comes in and go out, symptoms of disease, that can appear When Sahae lost homeostasis and the treatment principle. Yeong-wi-gi-hyeo (營衛氣血) enables complex vital phenomenon of human body. This Yeong-wi-gi-hyeo (營衛氣血) can not move if there is no systematic O-jang-yuk-bu (五臟六腑), Sip-yi-gyeong-maek (十二經脈) and Gi-gyeong-pal-maek (奇經八脈). For these system batch, it is Sahae do most important part. Sahae is synthetic and systematic concept. This chapter is explaining the position and function. Together, This chapter is presenting symptoms and treatment principle that can appear when Sahae overbalanced. This is offering important clue in Korean medicine physiology and pathology phenomenon study. Therefore, I gathers and compares and analyzed commentses of several doctors to grasp definitely this chapter's contents, and also investigated and translated. KCI Citation Count: 0